Effect of Problem-Based Learning with Interactive Animation Videos on Math Problem-Solving and Critical Thinking Skills - Suardika, I Made Dandi; Pujawan, I Gusti Ngurah; Divayana, Dewa Hendra (International Journal of Education, Management, and Technology, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on students' mathematical problem-solving skills, considering their critical thinking abilities. A quasi-experimental design with a 2x2 treatment-by-level approach was used, involving two groups: one using the PBL model and the other using conventional methods. The subjects were seventh-grade students at SMP Negeri 6 Singaraja. Data were collected through tests on mathematical problem-solving and critical thinking abilities. The results show that the PBL model significantly affects mathematical problem-solving skills, particularly for students with high critical thinking abilities. Students in the PBL group had an average score of 79.9, higher than those in the conventional group, who scored 56.6 on average. Moreover, the interaction between the teaching model and critical thinking abilities significantly influenced the outcomes. However, for students with low critical thinking abilities, the PBL model did not have a significant impact on their mathematical problem-solving skills. This study concludes that the PBL model is effective in improving problem-solving skills in students with high critical thinking abilities but may need adjustments for students with lower critical thinking skills.